Germ-Free Mice Under Two-Layer Textiles Are Fully Protected From Bacteria in Sprayed Microdroplets: A Functional in vivo Test Method of Facemask/Filtration Materials - Rodriguez-Palacios, Alex; Conger, Mathew; Cominelli, Fabio (Frontiers in Medicine, 2020)
Several studies have measured the effectiveness of masks at retaining particles of various sizes in vitro. To identify a functional in vivo model, herein we used germ-free (GF) mice to test the effectiveness of textiles as filtration material and droplet barriers to complement available in vitro-based knowledge. Herein, we report a study conducted in vivo with bacteria-carrying microdroplets to determine to what extent household textiles prevent contamination of GF mice in their environment. Using a recently validated spray-simulation method (mimicking a sneeze), herein we first determined that combed-cotton textiles used as two-layer-barriers covering the mouse cages prevented the contamination of all GF animals when sprayed 10–20 bacterial-droplet units/cm2. In additional to exposure trials, the model showed that GF mice were again protected by the combed-cotton textile after the acute exposure to 10 times more droplets (20 “spray-sneezes”, ~200 bacterial-droplet units/cm2). Overall, two-layer combed-cotton protected 100% of the GF mice from bacteria-carrying droplets (n = 20 exposure-events), which was significantly superior compared to 100% mouse contamination without textile coverage or when 95% partly covered (n = 18, Fisher-exact, p < 0.0001). Of relevance is that two different densities of cotton were equally effective (100%) in preventing contamination regardless of density (120–vs. 200 g/m2; T-test, p = 0.0028), suggesting that similar density materials could prevent droplet contamination. As a practical message, we conducted a speech trial (counting numbers, 1–100) with/without the protection of the same cotton textile used as face cover. The trial illustrated that contamination of surfaces occurs at a rate of >2–6 bacteria-carrying saliva-droplets per word (2.6 droplets/cm2, 30 cm) when speaking at 60–70 decibels and that cotton face covers fully prevent bacterial surface contamination.